Fate of aerosolized recombinant DNA-produced alpha 1-antitrypsin: use of the epithelial surface of the lower respiratory tract to administer proteins of therapeutic importance. - Hubbard, R C (1989)
To evaluate the possibility of administering therapeutic proteins via the respiratory route, we administered an aerosol of recombinant DNA-produced human alpha 1-antitrypsin (rAAT) to anesthetized sheep and measured levels of the protein in epithelial lining fluid (ELF), lung lymph, blood, and urine. Using a nebulizer that generated aerosol droplets with a mass median aerodynamic diameter of 2.7 micron (55% of droplets were less than 3 micron, a particle size optimal for deposition on the alveolar epithelium), in vitro studies demonstrated that the aerosolized rAAT remained intact and fully functional as an inhibitor of neutrophil elastase. When aerosolized to sheep, the 45-kDa rAAT molecule diffused across the alveolar epithelium, as evidenced by its presence in lung lymph and in blood. Comparison of ELF, lymph, blood, and urine rAAT levels demonstrated that the process was concentration dependent, with highest levels in ELF and in descending concentrations with approximately 10-fold concentration differences in each consecutive compartment, respectively. Importantly, evaluation with aerosolized 125I-labeled rAAT demonstrated that the rAAT molecules that reached the lung lymph and the systemic circulation remained intact as a 45-kDa protein. These results demonstrate the feasibility of using aerosolization to the pulmonary epithelial surface to administer sizeable proteins of therapeutic interest, thus circumventing the necessity of the traditional parenteral modes of administration of such molecules.